2015
DOI: 10.1007/978-3-319-20182-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Wine Brand Category Choice and Confucianism: A Purchase Motivation Comparison of Caucasian, Chinese and Korean Consumers

Abstract: Immigrants are an important demographic group who are increasingly targeted as consumers by the wine industry in Australia and other Western markets. These markets are often not homogenous as intra-national diversity has created a complex market place in many Western key markets. In this study, wine brand category choice for Chinese and South Korean consumers living in Australia was probed and contrasted with the choices of Caucasian consumers. Three purchase scenarios, namely self/household-consumption, socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
(32 reference statements)
0
12
0
1
Order By: Relevance
“…workforce. The study found evidence of Confucian Heritage Cultures (Lee, 1996;Monkhouse et al, 2013;Yao et al, 2015) with China, Japan and Korea distinct from the non-Confucian Asian countries in the study (India and Indonesia). As such a new term: Confucian Orbit is introduced for Korea, China and Japan, countries where performance has dramatically improved and reached, if not superseded, the West.…”
Section: Theoretical Implicationsmentioning
confidence: 64%
“…workforce. The study found evidence of Confucian Heritage Cultures (Lee, 1996;Monkhouse et al, 2013;Yao et al, 2015) with China, Japan and Korea distinct from the non-Confucian Asian countries in the study (India and Indonesia). As such a new term: Confucian Orbit is introduced for Korea, China and Japan, countries where performance has dramatically improved and reached, if not superseded, the West.…”
Section: Theoretical Implicationsmentioning
confidence: 64%
“…Government regulations implemented around the world are another area many stakeholders should take into account when designing any wine marketing plan [41]. Wine marketing provides a crucial contribution to the dynamics and performance of the sector around the world; however, its design is affected by several factors [42][43][44][45], where scientific research brings fundamental insights [46][47][48]. In any case, the social and cultural dimension of the wine should also be considered and explored within wine marketing plans [49,50].…”
Section: Supply Indexmentioning
confidence: 99%
“…December 2019 [105] A large portion of iGen (21)(22)(23)(24) and millennial (25)(26)(27)(28)(29) prefers sparkling wine fairly or a little sweet (54 and 46%, respectively). Millennial (30)(31)(32)(33)(34)(35)(36)(37)(38)(39), GenX (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54), and boomer (55-73) prefer sparkling wine somewhat or very dry (50, 66, and 76%, respectively).…”
Section: Months Opinionsmentioning
confidence: 99%
See 2 more Smart Citations